2006
DOI: 10.1007/s00122-005-0186-x
|View full text |Cite
|
Sign up to set email alerts
|

Population development by phenotypic selection with subsequent marker-assisted selection for line extraction in cucumber (Cucumis sativus L.)

Abstract: Cucumber (Cucumis sativus L.; 2n = 2x = 14) has a narrow genetic base, and commercial yield of US processing cucumber has plateaued in the last 15 years. Yield may be increased by altering plant architecture to produce unique early flowering (days to flower, DTF), female (gynoecious, GYN), highly branched (multiple lateral branching, MLB), long-fruited (length:diameter ratio, L:D) cultivars with diverse plant statures. The genetic map position of QTL conditioning these quantitatively inherited yield component … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
75
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 45 publications
2
75
0
1
Order By: Relevance
“…Information about gene action with regards to different traits will be helpful in selecting appropriate breeding procedures aimed at fruit yield improvement. There are different traits that are related to fruit weight and fruit number such as fruit length; fruit diameter; fruit length/diameter (L:D) ratio; vine length; leaf area that includes leaf length and leaf width (Hormuzdi and More 1989; Serce et al 1999;Lopez-Sese and Staub 2002;Shetty and Wehner 2002;Blanco et al 2005;Fan et al 2006;Afangideh and Uyoh 2007;Cho et al 2007;De Wilde and Duyfjes 2010); number of nodes per vine (Singh et al 2011); plant height (Mule et al 2011); and phenological traits including days to 50% flowering, anthesis, and first female flower formation (Singh et al 2011). Leaf area is an important variable for most physiological and agronomic studies involving plant growth, light interception, photosynthetic efficiency, evapotranspiration, or response to fertilizers and irrigation (Blanco et al 2005).…”
mentioning
confidence: 99%
“…Information about gene action with regards to different traits will be helpful in selecting appropriate breeding procedures aimed at fruit yield improvement. There are different traits that are related to fruit weight and fruit number such as fruit length; fruit diameter; fruit length/diameter (L:D) ratio; vine length; leaf area that includes leaf length and leaf width (Hormuzdi and More 1989; Serce et al 1999;Lopez-Sese and Staub 2002;Shetty and Wehner 2002;Blanco et al 2005;Fan et al 2006;Afangideh and Uyoh 2007;Cho et al 2007;De Wilde and Duyfjes 2010); number of nodes per vine (Singh et al 2011); plant height (Mule et al 2011); and phenological traits including days to 50% flowering, anthesis, and first female flower formation (Singh et al 2011). Leaf area is an important variable for most physiological and agronomic studies involving plant growth, light interception, photosynthetic efficiency, evapotranspiration, or response to fertilizers and irrigation (Blanco et al 2005).…”
mentioning
confidence: 99%
“…Simple, yet effective, markerassisted backcross introgression strategies may be effective for the introduction of plastomes and nuclear factors using the chloroplast markers identified by Chung et al (2003b) and Ali et al (2013). Such strategies have been effective in the introgression of yield and quality component traits in cucumber (Fazio et al, 2003;Fan et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In all of these studies, significant changes in allele frequencies were associated with chromosomal segments. In some studies, correspondences of loci identified by SM and QTL identified in biparental crosses were examined and often confirmed (Sughroue and Rocheford 1994;De Koeyer et al 2001;Smalley et al 2004;Fan et al 2006). In a study by Coque and Gallais (2006), a recurrently selected population derived from the same recombinant inbred line population in which QTL were initially identified was used to validate those QTL by SM.…”
mentioning
confidence: 98%
“…The authors are aware of only 10 studies that utilized artificially selected plant populations for QTL mapping (Stuber and Moll 1972;Stuber et al 1980;Sughroue and Rocheford 1994;Labate et al 1999;De Koeyer et al 2001;Smalley et al 2004;Li et al 2005;Fan et al 2006;Coque and Gallais 2006;Falke et al 2007), in contrast to the hundreds of studies that have identified QTL on the basis of traitmarker associations in unselected biparental mapping populations. There thus may be potential to take further advantage of the artificial selection exerted in plant or animal improvement programs to detect useful genetic variation.…”
mentioning
confidence: 99%
See 1 more Smart Citation